Monitoring Autophagy at Cellular and Molecular Level in Crassostrea gigas During an Experimental Ostreid Herpesvirus 1 (OsHV-1) Infection - Picot, Sandy; Faury, Nicole; Pelletier, Camille; Arzul, Isabelle; Chollet, Bruno; Dégremont, Lionel; Renault, Tristan; Morga, Benjamin (Frontiers in Cellular and Infection Microbiology, 2022)
Mortality outbreaks of young Pacific oysters, Crassostrea gigas, have seriously affected the oyster-farming economy in several countries around the world. Although the causes of these mortality outbreaks appear complex, a viral agent has been identified as the main factor: a herpesvirus called ostreid herpesvirus 1 (OsHV-1). Autophagy is an important degradation pathway involved in the response to several pathologies including viral diseases. In C. gigas, recent studies indicate that this pathway is conserved and functional in at least haemocytes and the mantle. Furthermore, an experimental infection in combination with compounds known to inhibit or induce autophagy in mammals revealed that autophagy is involved in the response to OsHV-1 infection. In light of these results, the aim of this study was to determine the role of autophagy in the response of the Pacific oyster to infection by virus OsHV-1. For this purpose, an experimental infection in combination with a modulator of autophagy was performed on Pacific oysters known to have intermediate susceptibility to OsHV-1 infection. In haemolymph and the mantle, the autophagy response was monitored by flow cytometry, western blotting, and real-time PCR. At the same time, viral infection was evaluated by quantifying viral DNA and RNA amounts by real-time PCR. Although the results showed activation of autophagy in haemolymph and the mantle 14 hours post infection (after viral replication was initiated), they were also indicative of different regulatory mechanisms of autophagy in the two tissues, thus supporting an important function of autophagy in the response to virus OsHV-1.